Expression of well-being in social networking sites : comparison between Twitter and Instagram - Ratmelia, Noverinda Bella (2018)
Usage of social networking sites (SNS) and subjective well-being (SWB) or simply wellbeing have been subject of research of many scholars. Current studies about SNS and well-being are mainly focused on activities on SNS such as liking, commenting, and information consumption, and its effect on well-being. However, there are very few studies that investigate whether users talk about topics related to well-being on SNS and if they do, what their sentiments are. SNS and media richness is also another popular topic of research. Current studies about SNS and media richness are mainly focused on the effect of media richness on SNS platform adoption, user engagement, etc. Few studies have explored media richness and sentiments as well as media richness and topics, especially those related to well-being on SNS. This study attempted to find out what are the well-being related topics that users talked about on Instagram and Twitter, including their sentiments about that particular topic and media type used on SNS by conducting a content analysis of their SNS posts. This study also compared the usage between the two SNS by the same users to determine the significance of the observed differences. A total of 44 users with Twitter and Instagram accounts were chosen as the sample of this study. Two coders were trained and then coded the SNS posts on three main aspects: the topic of the post, the sentiment, and media types used. For the topics, the study referenced the topics listed on OECD Better Life Index, with further modification based on multiple pilot testings. The results of this study showed that leisure activities, job, and humour are the most commonly talked about topics on both SNS. Majority of the posts have positive sentiments on most topics on both SNS, and the most popular media type is text and image for Instagram and text only for Twitter. Significant differences between the two SNS are observed on all sentiments, but only on some topics and media types. This study contributed to the knowledge about well-being on SNS as well as media richness on SNS. The study’s practical implication includes ideas to make a more interesting social media content, and potential usage in features and user experience design to enhance social networking sites. Finally, the results of this paper prompt many ideas for future research. For example, future studies could incorporate survey method alongside content analysis to examine the motivations behind choosing certain SNS or media types for different topics and/or sentiment.